2020
DOI: 10.37506/mlu.v20i1.350
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Medicolegal Autopsy Cases at Tertiary Care Centre in Belagavi, Karnataka. A One Year Retrospective Study

Abstract: Background: The profile of medico legal autopsy cases is important in order to know the death statistics in a region due to unnatural causes and also help to address the demographic needs according to the mortality statistics specific to that region.Materials and Methods: The present study is a retrospective study of autopsies performed at KAHER'S tertiary care centre K.L.E Hospital, Belagavi, Karnataka India in the year 2017. During this period a total of 159 autopsy cases were conducted. Relevant information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Similar findings were obtained by Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi. 4 Maximum cases (41) were from 21 to 30 years age group, followed by 31 to 40 (33 cases) and 41 to 50 (16 cases). Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi 4 also found similar results.…”
Section: Discussionmentioning
confidence: 96%
“…Similar findings were obtained by Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi. 4 Maximum cases (41) were from 21 to 30 years age group, followed by 31 to 40 (33 cases) and 41 to 50 (16 cases). Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi 4 also found similar results.…”
Section: Discussionmentioning
confidence: 96%
“…Medicolegal autopsies are fundamental component of an inquiry of unexpected suspicious death. Retrospective analysis of autopsy cases is usually performed to identify the frequency of unnatural cases of death of a particular area.This assists us to assess the demographic requirements depending on mortality figures particular to that area.It is also needed to stop the preventable fatalities in future and to examine the unpretentious crime rate of that area 2 .Medicolegal autopsy is executed on the demand of legal authority in situations linking to suspicious,sudden,unnatural,controversial or criminal deaths.The findings obtained are used for legal purposes so as to facilitate the course of justice 3 . Purpose of conducting postmortem investigation is to discover the identification of unknown dead body, determining the cause and timing of death,deciding the natural and unnatural mode of death,concluding whether it was homicidal,suicidal or accidental.For newly born babies, the inquiry of dead fetus should also be done 4 .…”
Section: Introductionmentioning
confidence: 99%